2005
DOI: 10.1002/cncr.20801
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of polyomavirus and herpesvirus types 6 and 7 in human lymphomas

Abstract: BACKGROUND The association of viruses with several human tumors has been studied for almost 100 years, and it remains a very controversial issue. Due to the fact that the presence of polyomaviruses and herpes viruses reportedly are associated with lymphomas, albeit with striking results and differences between the many studies, the authors undertook a study into the presence of viral sequences of polyomavirus (BK virus, JC virus, and especially simian virus 40 [SV40]) in human lymphomas in an attempt to explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Since BKV has been convincingly detected in peripheral blood cells of normal individuals [30,32,128], investigators began to look for an association between BKV and lymphoma. Only 5 out of 83 lymphoma samples were positive for BKV DNA using standard and real-time PCR [129]. Based on the higher percentage of normal BKV-positive lymphocytes routinely observed, this study does not support an association between BKV and lymphoma [30,32,128].…”
Section: Bk Virus and Human Tumorsmentioning
confidence: 84%
“…Since BKV has been convincingly detected in peripheral blood cells of normal individuals [30,32,128], investigators began to look for an association between BKV and lymphoma. Only 5 out of 83 lymphoma samples were positive for BKV DNA using standard and real-time PCR [129]. Based on the higher percentage of normal BKV-positive lymphocytes routinely observed, this study does not support an association between BKV and lymphoma [30,32,128].…”
Section: Bk Virus and Human Tumorsmentioning
confidence: 84%
“…Three studies that were primarily investigations of SV40 in lymphoma tissues detected no JCV or BKV DNA sequences in NHL tissues (20)(21)(22). Another laboratory reported JCV and BKV sequences in 5% and 6% of 83 lymphomas, respectively (18). Finally, a report of JCV DNA sequences identified 81% of 27 central nervous system lymphomas analyzed (19).…”
Section: Discussionmentioning
confidence: 99%
“…JCV has been shown to infect B-lymphocytes (14,15), and Neel and colleagues have described chromosomal damage in lymphocytes associated with both JCV (16,17) and BKV (16) infections. Some investigators have detected polyomavirus sequences from NHL tissues, including one laboratory that detected JCV and BKV sequences in 5% and 6% of 83 lymphomas, respectively (18) and a recent report that showed the presence of JCV DNA sequences in 22 of 27 B-cell lymphomas of the central nervous system, a subset of which also contained EBV DNA (19).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from serological experiments, a number of investigators have demonstrated a lack of significant SV40 seroprevalence in patients with NHL [71][72][73][74]. Though these noted studies [71][72][73][74] relied solely on serological evidence, PCR has been used to show that SV40 DNA sequences were either of low incidence in comparison to controls or unable to be detected in NHL samples from a variety of countries, including the United States [75][76][77][78][79].…”
Section: Non-hodgkin Lymphomamentioning
confidence: 95%